Leptomeningeal Dissemination in Gall Bladder Carcinoma: Sequelae of Long-Term Survival? - Shikha Goyal; Bidhu Kalyan Mohanti (Case Reports in Hepatology)
Patients with gall bladder malignancies usually present at an advanced stage with less than 20% cases being resectable at presentation and over a half harbouring distant metastases to liver or paraaortic nodes. Long-term cure is uncommon and so is the presence of central nervous system metastases. We present the case of a middle-aged woman with adenocarcinoma gall bladder, treated with postoperative locoregional irradiation following simple cholecystectomy, who developed headache, backache, vision loss, and multiple joint pains six years following adjuvant therapy. A diagnosis of leptomeningeal carcinomatous meningitis was established with cerebrospinal fluid cytology positivity for carcinoma. She deteriorated on palliative cranial irradiation and was managed with best supportive care.